2013
DOI: 10.1007/s00011-013-0629-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of interleukin 17A and interleukin 17F and their association with inflammatory bowel disease in a Chinese Han population

Abstract: The IL17F (rs763780, 7488T/C) variant was associated with an increased risk for the development of CD, and affected some clinical features of UC and CD. The IL17A (rs2275913, G-197A) variant had a weak association with the severity of UC. There was a risk haplotype in IL17A which could increase the risk of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 35 publications
2
32
0
1
Order By: Relevance
“…We also did not find any relationships between the IL-17A G197A polymorphism and susceptibility of RA. On the other hand, having A allele at the IL-17A G197A polymorphism site was found to be a protective factor in patients with ulcerative colitis (Zhang et al, 2013), whereas it was related with higher severity of mucosal inflammation in patients with gastric cancer (Shibata et al, 2009). Inconsistent with these results, we found possible relationships with DAS28 scores, VAS pain, and IL-17A G197A, but these associations did not reach a significant level.…”
Section: Discussionsupporting
confidence: 41%
“…We also did not find any relationships between the IL-17A G197A polymorphism and susceptibility of RA. On the other hand, having A allele at the IL-17A G197A polymorphism site was found to be a protective factor in patients with ulcerative colitis (Zhang et al, 2013), whereas it was related with higher severity of mucosal inflammation in patients with gastric cancer (Shibata et al, 2009). Inconsistent with these results, we found possible relationships with DAS28 scores, VAS pain, and IL-17A G197A, but these associations did not reach a significant level.…”
Section: Discussionsupporting
confidence: 41%
“…Multiple previous studies have reported an association between IL-17 gene polymorphisms and autoimmune diseases (Jin et al, 2011;Zhang et al, 2013;Maalmi et al, 2014;Shen et al, 2015). Jin et al (2011) reported an association between IL-17 gene polymorphisms and susceptibility to asthma in a Korean population, and suggested that the rs1889570 polymorphism was correlated with the development of asthma.…”
Section: Discussionmentioning
confidence: 96%
“…Maalmi et al (2014) conducted a study in a Tunisian population, and found that the IL-17A rs2275913 and IL-17F rs763780 were associated with an increased risk of asthma in children. Zhang et al (2013) examined the association between IL-17 gene polymorphisms and inflammatory bowel disease, and reported that the IL-17 rs2275913 and rs763780 polymorphisms were associated with an increased risk of inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A rs2275913 and IL-17F rs763780 are two common SNP loci in the IL-17 genes, and these two SNPs could influence the transcriptional regulation of IL-17. Previous studies have reported an association between IL-17A rs2275913 and IL-17F rs763780 and various diseases, such as inflammatory bowel disease, osteoarthritis, tuberculosis, and cancers (Zhang et al, 2013;Han et al, 2014;Bulat-Kardum et al, 2015;Gao et al, 2015). However, only two previous studies have reported an association between the IL-17A gene polymorphism and cardiovascular disease (Pei et al, 2009;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%